Optimal Export Policy for a New-Product Monopoly - Kyle Bagwell (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
A new welfare-enhancing role is identified for a policy of export subsidization in a new-product industry. An export subsidy policy promotes the (rational) perception that a high-quality export can be provided at a relatively low price. Thus, an export subsidy generates a first order benefit to welfare by enabling a high-quality export to be sold at a less-distorted, high price. The subsidy will also introduce distortions into the price of a low-quality export and, when product quality is policy-sensitive, the quality selection process. Since these choices are initially undistorted, however, the export-country welfare loss arising from new distortions is of second order importance.
Keywords: 330